1999
DOI: 10.1002/(sici)1097-0010(19990501)79:6<879::aid-jsfa295>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fish, starch and salt contents on the microstructure and expansion of fish crackers (‘keropok’)

Abstract: Light microscopy studies on the fish cracker gel and expanded product (‘keropok’) emphasised the role of fish proteins in the starch expansion process. The addition of salt (20 g kg−1) in the ‘keropok’ helped to distribute evenly the starch in the fish protein. Formation of thin fish muscle bundles assisted the expansion of ‘keropok’. At 700–900 g kg−1 fish content, the fish muscle bundles formed a continuous network that caused a drop in the ‘keropok’ expansion. From the scanning electron microscopy study, ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
2
7
0
1
Order By: Relevance
“…As previously mentioned, the lower degree of linear expansion is related to the increase of fish protein. Cheow et al (1999) studied the microstructure of fish crackers and found that poorlyexpanded fish crackers contained large aggregates of fish protein. This prevented the starch from expanding in hot cooking oil and made the filaments more dense and thick and the final result was the increase in the hardness value.…”
Section: Nwaoha and Itoje 079supporting
confidence: 88%
“…As previously mentioned, the lower degree of linear expansion is related to the increase of fish protein. Cheow et al (1999) studied the microstructure of fish crackers and found that poorlyexpanded fish crackers contained large aggregates of fish protein. This prevented the starch from expanding in hot cooking oil and made the filaments more dense and thick and the final result was the increase in the hardness value.…”
Section: Nwaoha and Itoje 079supporting
confidence: 88%
“…Based on the fact that wheat crackers have a global impact on nutrition and that variations of this product are well accepted (CHEOW et al, 2004;SALLEH et al, 2007;SINGHAL et al, 2008;SUBBA, 2002), we believe that the development of sensory acceptable fish crackers of high nutritional quality can be a successful strategy for increasing fish consumption and that fish crackers can be an alternative to high-calorie, low-nutritionalvalue, ready-to-eat food.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Before consumption, the dough is sliced, and the slices are fried in hot oil, which causes keropok to expand into a porous, low-density product (KYAW et al,1999). The effects of process parameters, as well as of the type and amount of starch, on the linear expansion and crunchiness of keropok after frying have previously been described (CHEOW et al, 2004;KYAW et al, 1999;KYAW et al, 2001b;MOHAMED et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Cheow et al (1999a) examined the effects of salt, sugar and MSG on viscoelastic properties of fish cracker gel. Cheow et al (1999b) studied the effect of salt and sugar on expansion and microstructure of fish crackers. Kyaw et al (1999) investigated the effect of steaming time on linear expansion of fish crackers.…”
Section: Introductionmentioning
confidence: 99%